Transjugular intrahepatic portosystemic shunt creation for cirrhotic portal hypertension is well tolerated among patients with portal vein thrombosis. Issue 6 (June 2018) - Merola, Jonathan; Fortune, Brett E.; Deng, Yanhong; Ciarleglio, Maria; Amirbekian, Smbat; Chaudhary, Noami; Shanbhogue, Alampady; Ayyagari, Rajasekhara; Rodriguez-Davalos, Manuel I.; Teperman, Lewis; Charles, Hearns W.; Sigal, Samuel H.
Abstract : Background: Portal vein thrombosis (PVT) develops in cirrhotic patients because of stagnation of blood flow. Transjugular intrahepatic portosystemic shunt (TIPS) creates a low-resistance conduit that restores portal venous patency and blood flow. Aim: The effect of PVT on transplant-free survival in cirrhotic patients undergoing TIPS creation was evaluated. Patients and methods: A multicenter, retrospective cohort study of patients who underwent TIPS creation for cirrhotic portal hypertension was carried out. A Cox model with propensity score adjustment was developed to evaluate the effect of PVT on 90-day and 3-year transplant-free survival. A subgroup analysis examining mortality of those with superior and inferior PVT was also carried out. Results: A total of 252 consecutive TIPS creations were assessed, including 65 in patients with PVT. Survival of patients with high Model for End-stage Liver Disease scores (≥18) and PVT was not statistically different compared with patients with low Model for End-stage Liver Disease scores (<18) and no PVT at 90 days ( P =0.46) and 3 years ( P =0.42). Those with superior PVT had improved 90-day and 3-year survival both compared with patients with a inferior PVT and those without a PVT ( P <0.01, all cases). Conclusion: The presence of PVT does not impair the prognosis of patients following TIPS creation, particularly in patients with superior portal occlusion.